1996
DOI: 10.1029/96gl01043
|View full text |Cite
|
Sign up to set email alerts
|

Zeeman splitting of the 61 Gigahertz oxygen (O2) line in the mesosphere

Abstract: Zeeman splitting of O2 molecular states in the Earth's upper atmosphere leads to polarized emission spectra. A 61 GHz radiometer operated as part of the Millimeter‐wave Atmospheric Sounder (MAS), a core payload instrument of the NASA Space Shuttle ATLAS missions, observed such emissions. This instrument's high resolution spectrometer (200 kHz) allows us to verify for the first time Zeeman effect model calculations for the upper atmosphere in some detail. The results suggest some interesting new aspects for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…We do not understand the reason for this discrepancy. Comparing our results with results of another model [10], Figure 2 of Hartmann et al [16], however, we find that the consistently concave shape is reproduced in ARTS but not by von Engeln [12]. This second comparison strengthens our belief that the implementation in ARTS is valid.…”
Section: Qualitative Test Resultssupporting
confidence: 87%
“…We do not understand the reason for this discrepancy. Comparing our results with results of another model [10], Figure 2 of Hartmann et al [16], however, we find that the consistently concave shape is reproduced in ARTS but not by von Engeln [12]. This second comparison strengthens our belief that the implementation in ARTS is valid.…”
Section: Qualitative Test Resultssupporting
confidence: 87%
“…Hartmann et al (1996) observed the Zeeman broadening of the oxygen emission line of the 9 + line in the 61.1509 ± 0.062 GHz frequency range using the Millimeter-Wave Atmospheric Sounder on the NASA space shuttle during the ATLAS missions. Comparison of satellite measurements and radiative transfer models including the Zeeman effect have also been addressed (Han et al, 2007(Han et al, , 2010Schwartz et al, 2006).…”
Section: F Navas-guzmán Et Al: Zeeman Effect Measurements In Atmospmentioning
confidence: 99%
“…The Zeeman effect must thus be taken into account by the radiative transfer schemes used as forward models for numerical weather prediction assimilations at the top of the modeled profiles. This has been pointed out by Lenoir (1967Lenoir ( , 1968, Liebe (1981), Rosenkranz and Staelin (1988), Hartmann et al (1996), Han et al (2007), Kobayashi et al (2009), and Stähli et al (2013), among others.…”
Section: R Larsson Et Al: High Altitude Ssmis: Radiative Transfer Mmentioning
confidence: 80%